ESG Integration in Investment Portfolios: A Comparative Study Between Developed and Emerging Markets - Dessy Evianti; Muhammad Yusuf; Lisdawati Lisdawati; Teddy Oswari; Ahmed Al-Fahad (Yayasan Adra Karima Hubbi, 2025)
The growing prominence of Environmental, Social, and Governance (ESG) principles has reshaped investment decision-making across global financial markets. While ESG integration is well established in developed economies, its adoption in emerging markets remains uneven due to institutional, regulatory, and data transparency disparities. This study aims to compare the performance, risk characteristics, and strategic integration of ESG factors within investment portfolios across developed and emerging markets. A mixed-method approach was applied, combining quantitative analysis of ESG-indexed equity portfolios from 2015 to 2023 with qualitative evaluation of policy frameworks and investor behavior. The findings reveal that portfolios in developed markets consistently demonstrate superior risk-adjusted returns, attributed to stronger ESG disclosure standards and regulatory enforcement. Conversely, emerging markets exhibit higher return volatility and weaker ESG score correlations with financial performance, primarily due to inconsistent reporting and limited corporate accountability. The study concludes that while ESG integration enhances portfolio resilience and long-term sustainability, its impact is significantly conditioned by market maturity, governance quality, and institutional capacity. These results highlight the necessity for harmonized ESG frameworks and capacity-building initiatives to bridge the performance gap between developed and emerging economies.